Description of Alpheus buckupi spec. nov., a new amphi-Atlantic snapping shrimp (Caridea: Alpheidae), based on morphological and molecular data - Almeida, Alexandre O.; Terossi, Mariana; Araújo-Silva, Catarina L.; Mantelatto, Fernando L. (Zootaxa, 2013)
A new amphi-Atlantic snapping shrimp of the genus Alpheus Fabricius, 1798, Alpheus buckupi spec. nov., is described and illustrated based on material collected from the western (Orinoco Delta, Venezuela to São Paulo, Brazil) and east-ern Atlantic (São Tomé and Príncipe). The new species is morphologically similar to members of the A. lobidens De Haan, 1850 species complex, from the Indo-Pacific, including A. inopinatus Holthuis & Gottlieb, 1958 from the eastern Mediterranean, and the Red Sea to Pakistan, especially based on major and minor chelae configuration. We also char-acterized this new species in terms of DNA sequences of a ribosomal 16S subunit and compared it in a phylogenetic context. These analyses showed a clear separation of the specimens of A. buckupi spec. nov. from similar species of the A. edwardsii (Audouin, 1826) species group, including some morphologically close species such as A. cf. lobidens, A. heterochaelis Say, 1818, A. pontederiae de Rochebrune, 1883, A. sp. aff. euphrosyne De Man, 1897, and A. micro-rhynchus De Man, 1897.